2008
DOI: 10.1116/1.2841520
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of carbon nanotubes on constantan (Cu–Ni–Mn alloy) metallic substrates without adding additional catalysts

Abstract: In this study, metallic constantan (Cu55–Ni44–Mn1wt%) alloy substrates were investigated as an alternate choice of substrates to grow carbon nanotubes (CNTs). No additional catalysts were used other than the as-rolled and annealed substrates to process CNTs on them. High density CNT growth was observed to take place on these substrates when suitable conditions were used in a thermal chemical vapor deposition (CVD) furnace with C2H2 as the carbon precursor. Scanning electron microscopy and transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…5a shows a typical SEM image for both alloys in which nanofibers with diameters larger than 100 nm are observed, along with nanofibers thinner than 50 nm. Varanasi et al [33] also observed a wide range of CNTs diameters, 20-100 nm, grown on other Ni/copper substrate (Cu:Ni:Mn; 55:44:1 wt.%). Moreover, our results agree with observations of Tribolet et al [16] who observed thicker CNFs on stainless steel, as compared to Ni, grown on metallic filters from C 2 H 6 /H 2 at 620-680 °C after oxidation/reduction pretreatment.…”
Section: 4mentioning
confidence: 92%
See 1 more Smart Citation
“…5a shows a typical SEM image for both alloys in which nanofibers with diameters larger than 100 nm are observed, along with nanofibers thinner than 50 nm. Varanasi et al [33] also observed a wide range of CNTs diameters, 20-100 nm, grown on other Ni/copper substrate (Cu:Ni:Mn; 55:44:1 wt.%). Moreover, our results agree with observations of Tribolet et al [16] who observed thicker CNFs on stainless steel, as compared to Ni, grown on metallic filters from C 2 H 6 /H 2 at 620-680 °C after oxidation/reduction pretreatment.…”
Section: 4mentioning
confidence: 92%
“…The deposition of different carbon structures on metal foils by the catalytic decomposition of hydrocarbons at high temperatures (450-850 °C) has already been described in the literature [24][25][26][27]. Over the last decade, Ni, Fe, Co and stainless steel foils have been known for growing carbon nanostructures [28][29][30][31][32][33][34]. However, these studies are generally limited to just one type of metal foil, either pure metal or a specific metal alloy.…”
Section: Introductionmentioning
confidence: 99%
“…CVD is the most cost effective and promising one among different methods. Currently, the formation of CNTs directly on the metal plate by CVD has attracted much attention [10]. This is because the metal plate can act as the substrate and a catalyst for the growth of the CNTs at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesizing CNTs directly on metallic layers simplifies the electrode assembly process by avoiding transfers that require binders and conductive additives . Therefore, the direct synthesis of CNTs on metal substrates using chemical vapor deposition (CVD) has attracted much attention in recent years. VACNTs synthesized on metallic layers can also be used for field emission, nanoscale electronic devices, lithium-ion batteries, and supercapacitors. , A few teams have reported VACNT syntheses on various metal substrates such as stainless steel (SS), silver (Ag), gold (Au), and aluminum (Al) . However, all the reported CNT carpets, which were directly grown on metallic layers, have heights in the range of tens of microns.…”
Section: Introductionmentioning
confidence: 99%